Iatrogenic diaphragmatic hernia as a late complication of laparoscopic excisional biopsy of peritoneal nodules: A case report. (2020) - Hashimoto, Kyoichi; Obama, Kazutaka; Tsunoda, Shigeru; Hisamori, Shigeo; Nishigori, Tatsuto; Sakaguchi, Masazumi; Ueda, Yoko; Nakanishi, Nozomu; Sakai, Yoshiharu
Highlights: We report a rare case of delayed diaphragmatic hernia caused by laparoscopic biopsy. Coagulation for hemostasis after biopsy could cause diaphragmatic hernia. The heat by soft coagulation might unexpectedly damage diaphragmatic muscle. Abstract: Introduction: Iatrogenic diaphragmatic hernias have been reported as a rare complication of abdominal surgery, and only a few reports have suggested minimal intraoperative injury to the diaphragm as a cause. Presentation of case: We report a rare case of delayed diaphragmatic hernia caused by laparoscopic excisional biopsy of a peritoneal lesion on the diaphragmatic peritoneum. A 70-year-old woman with gastric gastrointestinal stromal tumor underwent laparoscopic partial gastrectomy and excisional biopsy for white nodules on the left diaphragmatic peritoneum using laparoscopic scissors. Slight bleeding that occurred after excisional biopsy was stopped using a soft-coagulation system. Six months after her first surgery, a left diaphragmatic defect and transverse colon migration into the thoracic cavity were detected on computed tomography. The patient subsequently underwent laparoscopic diaphragmatic hernia repair. The site at which the diaphragm defect occurred was consistent with the site of excisional biopsy. The defect was closed with interrupted suturing using non-absorbable threads, following which a composite mesh was applied above the suture site for reinforcement. Discussion: This is the first report of an iatrogenic diaphragmatic hernia after diagnostic laparoscopy for peritoneal excision biopsy of the diaphragmatic surface. In the present case, the coagulation procedure for hemostasis after peritoneal resection was considered to be the cause of the diaphragmatic hernia. The heat generated by soft coagulation might have unexpectedly reached and damaged the deep areas of the diaphragmatic muscle. Conclusion: Surgeons performing laparoscopic excisional biopsy of the diaphragmatic peritoneum should consider the potential risk for iatrogenic diaphragmatic hernias.